Steps in Designing Queue and Interview Process using Information System: A Case of Re-registration of New Students in Universitas Negeri Makassar - Ahmar, Ansari Saleh; Rusli, Rusli; Rahman, Abdul (The Asian Journal of Technology Management (AJTM), 2016)
Abstract. Universitas Negeri Makassar (UNM) have a number of prospective students is quite a lot. Based on data released by the BAPSI UNM (2015) that the data student candidates of UNM who passed the selection with SNMPTN SBMPTN selection as 3,791 people. If the prospective graduate students interviewed are normally it will take a long time and will certainly make students uncomfortable. Therefore it is necessary design an information systems to solving this problem. This research aimÂ  to develop an information system to facilitate the process queue. The method used in this research is to use the three stages in the Software Development Life Cycle method namely Initiation Phase, Development/Acquisition Phase, and Implementation Phase. This information system development using PHP and CodeIgniter as a its framework. This design results will be obtained an queues and interviews information system that can be used to manage the queue and interview data. By implementing this system, it potentially reduce time to wait and the process of managing results of interviews can be obtained directly without a process of inputting interview repeat if done manually.Keywords: Â Information System, Interview, Queue, re-registration of new student, Universitas Negeri Makassar.